Assessing the determinants and risk moderation in banking performance - Lubis, Jisman Mangitar; Moeljadi; Ratnawati, Kusuma; Djazuli, Atim (Asian Economic and Financial Review, 2025)
The study examines the factors affecting banking performance from 2014 to 2021, with a focus on the moderating role of bank risk. Internal factors explored include net interest margin (NIM), non-performing loans (NPL), good corporate governance (GCG), and the loan-to-deposits ratio (LDR). External factors, such as oil prices and a pandemic dummy variable representing COVID-19 versus pre-pandemic periods, are also analyzed. Banking performance is assessed through price-to-book value (PBV), return on assets (ROA), and return on equity (ROE). The results show NIM significantly influences PBV but not ROA or ROE. NPL significantly affects ROA and ROE while showing no impact on PBV. GCG positively impacts PBV but does not significantly affect ROA or ROE. LDR significantly improves ROA and ROE but has no effect on PBV. Bank risk weakens the effect of LDR, NPL, and the pandemic dummy on ROE, while also moderating the influence of GCG, NIM, and the pandemic dummy on PBV. However, it is not significant for key relationships involving oil prices. By analyzing both internal and external contributions to banking performance, this study provides insights into how these factors and risk interactions shape key metrics like PBV, ROA, and ROE.